Perinatal Outcomes of Multiple Births: Assessment of Morbidity and Mortality Rates in a Neunatal Care Unit - Haddad, Ahmed Isam Hameed; Alwan, Luay Hasan; Majeed, Amal Salman (Academic Journal of Clinicians, 2024)
A prospective study was carried out in the 1PstP neonatal care unit of Basrah Maternity and Children Hospital on 164 multiple births out of 1797 neonates were admitted to the unit during a period of 12 months. The multiples diseases and deaths were studied in relation to neonatal, labour, delivery and maternal characteristics from data collected by special questionnaire. Multiples account for (1.7%) from total births in the hospital. Mean gestational age was (34±0.30 week) and their mean weight was (1732± 44.17 grams). This study found that (76.2%) were preterm (<37 week), and (89%) were of low birth weight (< 2500g). A percent of (84.1) from multiples mothers were in the reproductive age group, and (72.6%) for low educated mothers, and (27.4%) of multiples were for induced pregnancies (by ovulation drugs or In Vitro Fertilization), while (72.6%) were for spontaneous pregnancies, and (65.2%) of multiples had complications during labour and delivery. Forty (24.3%) of Multiples died, which represent (12.9%) from total deaths in the 1PstP NCU. Deaths were more among male, and male to female ratio was (1.9:1). All deaths were due to respiratory distress syndrome. Factors like prematurity, low birth weight, need for resuscitation and low Apgar score at birth, maternal complications at labour and delivery and history of induced pregnancy (especially IVF) were associated with increase multiples death, and results were statistically significant. So prevention of preterm delivery, skilled attendance at birth with availability of surfactant and active ventilation with efforts to reduce maternal complications at delivery as possible are recommended.